0.2(8-6h)=h

Simple and best practice solution for 0.2(8-6h)=h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.2(8-6h)=h equation:


Simplifying
0.2(8 + -6h) = h
(8 * 0.2 + -6h * 0.2) = h
(1.6 + -1.2h) = h

Solving
1.6 + -1.2h = h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1h' to each side of the equation.
1.6 + -1.2h + -1h = h + -1h

Combine like terms: -1.2h + -1h = -2.2h
1.6 + -2.2h = h + -1h

Combine like terms: h + -1h = 0
1.6 + -2.2h = 0

Add '-1.6' to each side of the equation.
1.6 + -1.6 + -2.2h = 0 + -1.6

Combine like terms: 1.6 + -1.6 = 0.0
0.0 + -2.2h = 0 + -1.6
-2.2h = 0 + -1.6

Combine like terms: 0 + -1.6 = -1.6
-2.2h = -1.6

Divide each side by '-2.2'.
h = 0.7272727273

Simplifying
h = 0.7272727273

See similar equations:

| 14x^2-11xy-15y^2=0 | | 3x+47=180 | | 12.25-.75=x | | 4+(a/5)=2 | | 1+6=3+2x | | -3(3y-4)-y=-2(y-4) | | 1-9/6x=2/5 | | 1+3y=5/3y | | (3x-1)/4=-5/11 | | 2/3(6y+9)=20 | | 4(x-1)-2(3x+5)=3x-1 | | a+2b=50 | | 5x=3/7 | | 5x^3=3x^2 | | 12+3p=2p+4 | | 2x=3y-10 | | A=5k/7y | | 12x-8=-20 | | 3x+5=9y-4+z | | a+a+7=3+a | | 3[4(3x+1)-(10x-9)]=7x+9 | | x=2y^2-4 | | (2x-3)/4=(3-2x)/6 | | 2x-(1/x)=1 | | x^2-x-x=0 | | 2X+7X-12=33 | | X^2-2x-12=-12 | | 7(t-6)+7t=7(2t+3)-10 | | -6=(y-4)/9 | | 1/2(4y+3)=1/4(y+8) | | 7y+12/t=36 | | 61=6x-11 |

Equations solver categories